Viral infections of humans : epidemiology and control - Stanberry, Lawrence R.; Le Duc, James W.; Kaslow, Richard A. (Springer US, 2014)
Striking changes have occurred in the world since the publication of the last edition of Viral Infections of Humans. The global population is rapidly approaching 8 billion; climate change is leading to the introduction of new hosts, vectors and virus diseases heretofore never seen in many parts of the world; technological advances have revolutionized the ability to recognize and characterize viruses new and old; vaccines are altering the epidemiological landscape of the diseases they target, in some cases raising the hope of their eradication; and remarkably powerful computational tools are enabling not only detection of outbreaks of disease much sooner than in the past but also, through complex mathematical modeling, more accurate prediction of their potential impact. The new Fifth Edition of Viral Infections of Humans captures both the excitement and frustration of the dynamic struggle between humankind and the viruses that continue to cause immense suffering.  It presents the latest concepts, methods, and technologies in epidemiology, detection, investigation, modeling, and intervention.  Updated and entirely new chapters by dozens of experts across the field provide analytic summaries of current knowledge of viruses and prions causing acute syndromes, chronic illnesses, and/or malignancies.  In sum, this ambitiously expanded volume offers a uniquely comprehensive perspective on viruses in humans, from agents of classic diseases (e.g., hepatitis, measles, polio, rabies, and yellow fever), to those with greatest pandemic impact (e.g., influenza and human immunodeficiency virus), to those discovered relatively recently (e.g., henipavirus, metapneumovirus, and norovirus).  The new Fifth Edition of Viral Infections of Humans is an invaluable reference for  students, fellows and established professionals in the fields of microbiology, public health and infectious disease epidemiology, medicine, and health policy.